2011
DOI: 10.1111/j.1574-695x.2010.00757.x
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acid stimulates interleukin-23 production by peripheral blood mononuclear cells exposed to bacterial lipopolysaccharide

Abstract: Lactic acid is the predominant acid present in the vagina. We evaluated the consequences of lactic acid, at physiological levels present in the vagina, on cytokine responses of peripheral blood mononuclear cells (PBMCs) obtained from 10 individuals in the presence or absence of bacterial lipopolysaccharide. Preincubation of PBMCs in 15 mM lactic acid before the addition of lipopolysaccharide resulted in a 246% mean increase in interleukin-23 (IL-23) secretion over that released in the presence of lipopolysacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 33 publications
1
41
0
3
Order By: Relevance
“…In the presence of a synthetic analogue of double-stranded viral RNA, lactic acid potentiates the production of protective pro-inflammatory cytokines by vaginal epithelial cells. 29 Lactic acid also promotes activation of the T helper type 17 subclass of helper T lymphocytes, 30 stimulates dendritic cell maturation 31 and induces interferon-c production. 32 Each of these activities enhances activation of anti-microbial innate or acquired immunity.…”
Section: Vaginal Lactic Acidmentioning
confidence: 99%
“…In the presence of a synthetic analogue of double-stranded viral RNA, lactic acid potentiates the production of protective pro-inflammatory cytokines by vaginal epithelial cells. 29 Lactic acid also promotes activation of the T helper type 17 subclass of helper T lymphocytes, 30 stimulates dendritic cell maturation 31 and induces interferon-c production. 32 Each of these activities enhances activation of anti-microbial innate or acquired immunity.…”
Section: Vaginal Lactic Acidmentioning
confidence: 99%
“…The acidic environment provides optimal conditions for the lactobacilli and unfavourable growth conditions for the pathogenic micro-organisms (1,16). Lactic acid has been also shown to stimulate the immune response (17). In vitro experiments with L. acidophilus KS400 have demonstrated that the strain is able to produce substantial amounts of lactic acid (16).…”
Section: In Vitro Properties Of Lactobacillus Acidophilus Ks400mentioning
confidence: 99%
“…The vaginal stratified epithelium produces glycogen and other carbohydrates that are used by Lactobacillus species to produce lactic acid ; in return, the acidic environment protects the vaginal mucosa from colonization with pathogens such as Neisseria, other Gramnegative bacteria, and even HIV virus (Graver and Wade, 2011;Lai et al, 2009;Witkin et al, 2011). Lactobacilli may also protect against pathogenic bacteria through the production of bacteriocins such hydrogen peroxide (Fichorova et al, 2011;Hawes et al, 1996;Hillier et al, 1993).…”
Section: The Vaginal Microbiomementioning
confidence: 99%